Quantitative Analysis of European Union Agriculture Performance - Marian Reiff; Kvetoslava Surmanova; Adam P. Balcerzak; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2016)
The main aim of the article is to analyze differences of agriculture performance across the European Union countries in the years 2010-2013. The special attention was devoted to the results obtained by New Member States. The research was conducted with application of multiple criteria analysis tools: the method proposed by Hellwig and Ward's clustering method. The research was based on the collection of the World Bank development indicators. It confirms the existence of significant disparity in the performance of agricultural sector between the old and new member states that joined the UE after the year 2004.
Keywords: C38; O13; 330; Multiple Criteria Decision Analysis (MCDA); Hellwig Method; Cluster analysis; Economic performance; Agriculture